Decoding Secure AI Deployment in Cloud Environments - Bhaskar Goyal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Securing artificial intelligence deployments in cloud environments requires a comprehensive, multi-layered approach addressing unique challenges across physical, network, compute, storage, and application layers. This comprehensive examination explores the intricate security considerations essential for robust AI deployments in cloud environments, emphasizing Identity and Access Management as the cornerstone of defense strategies. With cloud-based AI spending projected to reach $97.7 billion by 2025 and 64% of enterprises storing sensitive data in public clouds, the stakes have never been higher. Advanced encryption technologies, including AES-256 with proper key rotation and emerging homomorphic approaches, demonstrate remarkable effectiveness in preventing data breaches, despite some performance tradeoffs. Secure development practices incorporating adversarial testing and bias detection mechanisms prove critical in preventing vulnerabilities at their source, with systematic red-team evaluations identifying 91.6% of potential attack vectors compared to just 34.5% through conventional methods. Regulatory compliance frameworks across GDPR, HIPAA, and financial services demand specialized approaches, with privacy-by-design principles significantly reducing both incidents and associated costs. The integration of AI-powered security tools throughout the technology stack creates a virtuous cycle where artificial intelligence both requires and enables stronger protection mechanisms, ultimately reducing breach impact and improving threat detection capabilities.
Keywords: Cloud security; artificial intelligence; identity management; encryption; regulatory compliance; zero trust architecture